2010
DOI: 10.1577/m10-033.1
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of Smallmouth Bass from a Simulated Tournament Weigh‐In Site

Abstract: Simulated smallmouth bass Micropterus dolomieu fishing tournaments were staged in Dale Hollow Lake, a 12,400‐ha reservoir in Tennessee, between March 2004 and February 2005 to investigate posttournament dispersal. Smallmouth bass (n = 54) were captured with conventional hook‐and‐line tackle and artificial lures, placed in live wells, and subjected to a weigh‐in procedure before being externally tagged with an ultrasonic transmitter and released. Water temperatures ranged from 7.4°C to 29.3°C (mean [SE] = 17.6°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Most fish that crossed into the Vermont Islands lake region did so in the northern reaches of the lake, near Isle La Motte, where water depth is 15-24 m, rather than crossing deep, pelagic zones (>60 m depth) east and southeast of Plattsburgh. These results support previous research that found that the vast majority of tournamentreleased Largemouth Bass used continuous shoreline for traveling and avoided deep, open water (Gilliland 1999) and that Smallmouth Bass dispersing from a central release point were rarely observed in open-water areas (Kaintz and Bettoli 2010).…”
Section: Dispersalsupporting
confidence: 90%
See 1 more Smart Citation
“…Most fish that crossed into the Vermont Islands lake region did so in the northern reaches of the lake, near Isle La Motte, where water depth is 15-24 m, rather than crossing deep, pelagic zones (>60 m depth) east and southeast of Plattsburgh. These results support previous research that found that the vast majority of tournamentreleased Largemouth Bass used continuous shoreline for traveling and avoided deep, open water (Gilliland 1999) and that Smallmouth Bass dispersing from a central release point were rarely observed in open-water areas (Kaintz and Bettoli 2010).…”
Section: Dispersalsupporting
confidence: 90%
“…Because black bass are thought to navigate primarily with the use of landmarks (Warden and Lorio 1975;Wilde 2003), postrelease movement patterns in waterbodies with large, deep pelagic zones may be limited (Healey 1990;Gilliland 1999;Kaintz and Bettoli 2010). Impediments to movement, such as pelagic zones and an absence of recognizable landmarks, can result in increased densities of fish located near release sites.…”
mentioning
confidence: 99%
“…Descended fish, on average, moved similar distances to the control group, and the farthest traveling fish in the study (28.6 km) was a descended individual. Stockpiling of fish following CFEs, defined as delayed or failed evacuation from the release site, is a concern for fisheries management and has been the subject of many other tracking studies (e.g., Richardson-Heft et al 2000;Young and Isely 2006;Kaintz and Bettoli 2010;Brown et al 2015). Our findings suggest that descending Walleye may be a better approach than venting for encouraging longer and faster movements away from CFE weigh stations after barotrauma relief.…”
Section: In Situ Telemetry Studymentioning
confidence: 74%
“…We first tagged fish with a unique cinch-up tag (FT-4; Floy Tag Manufacturing Inc.) behind the first dorsal fin. We attached acoustic transmitters to the tag loop either directly through the transmitter cap (for 142-d transmitters) or with PDSII 2-0 violet monofilament dissolvable suture (Ethicon, San Lorenzo, Puerto Rico) for 6-d transmitters such that transmitters would fall off after the monitoring period (modified from Kaintz and Bettoli 2010). The tagging and transmitter attachment procedure took approximately 2 min per fish, and we submerged fish in water the entire period.…”
Section: In Situ Telemetry Studymentioning
confidence: 99%
“…Transmitters were attached to the cinch‐up tag via a loop of Monocryl 2‐0 dissolvable suture. The suture material dissolves in approximately 21–30 d, allowing the radio or acoustic transmitter to release after a short‐term study (modified tagging methods from Kaintz and Bettoli ). The radio transmitters used were Lotek MCFT2‐3A and MCFT2‐3BM models (temperature and motion loggers) (Lotek Wireless, Newmarket, Ontario) that had a battery life of approximately 33 d. The acoustic tags used were Vemco V9‐2x and V13‐1x with external mounting caps for attachment (Vemco, Bedford, Nova Scotia); battery life ranged from 15 to 72 d. The attachment process took approximately 2 min, during which fish were kept submerged in the holding tank to limit their exposure to air.…”
Section: Methodsmentioning
confidence: 99%